UV Pulse Sequence-Dependent Properties of Al2O3 Films Via UV-Assisted Atomic Layer Deposition - Shin, Jin Kyeong; Eun, Su Min; Choi, Yeong Tae; Choi, Byung Joon (Archives of Metallurgy and Materials, 2026)
Uniform thin-film deposition on temperature-sensitive or particulate substrates remains challenging at low temperatures. Energy-enhanced atomic layer deposition offers an effective approach to activate surface reactions by supplying external energy such as plasma, mechanical input, or photon irradiation. In this work, Al2O3 thin films were deposited at a low temperature of 85°C by UV-assisted atomic layer deposition, and the effects of UV irradiation conditions on film properties were investigated. Under UV irradiation, the growth rate increased, while surface roughness and residual carbon content decreased, accompanied by an increase in the Al–O bonding fraction. These results demonstrate that UV-assisted atomic layer deposition enables high-quality Al2O3 coatings even under low-temperature conditions and suggest its potential applicability to powder surface modification processes.